The growing burden of generalized myasthenia gravis: a population-based retrospective cohort study in Taiwan - Herr, Keira Joann; Shen, Shih-Pei; Liu, Yanfang; Yang, Chih-Chao; Tang, Chao-Hsiun (Frontiers in Neurology, 2023)
Background The prevalence of myasthenia gravis is increasing in many countries, including Asia. As treatment options expand, population-based information about the disease burden can inform health technology assessments. Methods We conducted a population-based retrospective cohort study using the Taiwan National Healthcare Insurance Research database and Death Registry to describe the epidemiology, disease burden and treatment patterns of generalized myasthenia gravis (gMG) from 2009 to 2019. Episodes of hepatitis B virus (HBV) infection or reactivation were explored. Results The number of patients with gMG increased from 1,576 in 2009 to 2,638 in 2019 and the mean (standard deviation) age from 51.63 (17.32) to 55.38 (16.29) years. The female:male ratio was 1.3:1. Frequently reported co-morbidities were hypertension (32–34% of patients), diabetes mellitus (16–21%) and malignancies (12–17%). The prevalence of patients with gMG increased annually from 6.83/100,000 population in 2009 to 11.18/100,000 population in 2019 (p < 0.0001). There was no temporal trend in all-cause fatality rates (range 2.76–3.79/100 patients annually) or gMG incidence rates (2.4–3.17/100,000 population annually). First-line treatment was with pyridostigmine (82%), steroids (58%), and azathioprine (11%). There was minimal change in treatment patterns over time. Among 147 new HBV infections, 32 (22%) received ≥4 weeks of antiviral therapy suggesting chronic infection. The HBV reactivation rate was 7.2%. Conclusion The epidemiology of gMG in Taiwan is evolving rapidly, with higher prevalence rates and increasing involvement of older age-groups suggesting a growing burden of disease and associated healthcare costs. HBV infection or reactivation may pose a previously unrecognized recognized risk for patients with gMG receiving immunosuppressants.